色身与土地 ：台湾法鼓山「骨灰植存」之考察 = The physical body and land : observation from the ash burials of Taiwan Dharma drum mountain - 周佩镁 Chiew, Pui Mei (2015)
自古以来，百行以孝为先，将家中长辈的遗体入土为安就成了华人传统中根深蒂固的观念，若要改变，就要有适当的宣导与教育。佛教的丧葬传统是简礼薄葬，而华人的丧葬传统则是繁文缛节，排场越隆重，越孝顺。传统丧葬的方式从最原始的土葬到火化入塔，都因为“只进不出”而造成空间无法有效应用。时代变迁，无论是中国、台湾还是新加坡，这些人口密度高的国家都面临土地匮乏，因此政府不得不进行丧葬改革，实行平坟和环保自然葬。近年来，法鼓山和慈济等佛教团体都把佛法和环保融合到生活中，如心灵环保和环保自然葬。法鼓山创办人——圣严法师更以身说教，以「骨灰植存」的方式葬在法鼓山生命园区，从而达到了抛砖引玉的效果。本文将会简单介绍台湾佛教四大山头之一——法鼓山，并以法鼓山所推广的环保自然葬——骨灰植存为例, 透过汉传佛教中「有」和「无」的观念，探讨华人对于往生者遗体与土地之间的关系。同时，从环保的角度出发，探讨传统殡葬带来的环境问题与环保自然葬带来的利益。此外，本文也会探讨骨灰植存在新马华人社会的推广、发展以及影响发展的人文因素。Since the ancient times, filial piety is mostly concerned in the Chinese society. The Chinese have their own tradition for funeral matters to show that the family members are filial and respect the deceased, which is inhumation. In order to change, we must have the appropriate advocacy and education. Basically, the Buddhist funeral ceremony is conducted in a solemn and simple way, while the traditional Chinese funeral ceremony is conducted with the grand and complicated method. The traditional burial and cremation need a lot of permanent land for cemetery used and it’s causing environmental pollution, shortage of land and “dead graves” problems. Those high population density countries, such as China, Taiwan and Singapore, are facing the shortage of land, so the government of these countries had to realize the important of burial reform and natural burials. In these years, Dharma Drum Mountain, Tzu Chi and other Buddhist associations have spread the concept of “Integrate Dharma into Daily Life”, such as Spirit and Environmental Protection and Environmental Protection. Founder of Dharma Drum Mountain - Master Sheng Yen has sets an example for us, he decided to bury himself at the Dharma Drum Mountain Life Center with the “ash burials” method after his death. This article will briefly introduce the history of Dharma Drum Mountain, the concept of Master Sheng Yen, and the natural burials method suggested by Master Sheng Yen, which is “ash burials”. Through the Buddhism "You" and "Wu" concept, this article aims to figure out the connection of the Chinese, the remains of the deceased, and the land. From the perspective of environmental protection, this article also aims to investigate the pollution problems caused by the traditional burial and cremation. Besides, this article will also explore the possibility of the implementation of “ash burials” in Singapore and Malaysia.